The Philosophy of Multiculturalism: An Epistemological and Ethical Framework for Creating a Culture of Peace in Schools - Kerihi, Eka Citra Gayatri; Suastra, Wayan; Atmaja, Ananta Wikrama Tungga; Tika, I Nyoman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The phenomenon of intolerance and violence in the school environment is a problem that has continued to escalate in recent years. The minimal understanding of multiculturalism and the weak internalization of values of diversity make social interaction in schools vulnerable to conflict, prejudice, discrimination, and dehumanization. This article aims to philosophically examine the concept of multiculturalism as a basis for strengthening character education and a culture of peace in schools. By utilizing a literature review research method, this study integrates philosophical ideas of multiculturalism from contemporary literature, studies on inclusive education, and multicultural-nuanced learning models. This article finds that the philosophy of multiculturalism offers a relevant ethical and epistemological framework for modern education, especially in supporting harmonious student relationships, conflict management, and the strengthening of tolerance values. The discussion focuses on three main aspects: 1). The philosophical understanding of multiculturalism which serves as a conceptual basis for the construction of diversity awareness; 2). Its application in the educational environment, including curriculum, school culture, and educational leadership practices; and 3). Multicultural learning methods that allow for the more concrete internalization of values through dialogue, collaboration, and critical reflection. The research results affirm that educational institutions have a central role in instilling multicultural awareness from an early age, thereby being able to prevent acts of intolerance and violence. This article contributes to the development of the philosophy of education discourse by offering a comprehensive approach that can be used as a reference in designing inclusive, humanist, and socially just policies and learning practices.